Epicureanism: A Very Short Introduction - Wilson, Catherine (New York Oxford University Press, 2015)
Epicureanism is commonly associated with a carefree view of life and the pursuit of pleasures, particularly the pleasures of the table. However it was a complex and distinctive system of philosophy that emphasized simplicity and moderation, and considered nature to consist of atoms and the void. Epicureanism is a school of thought whose legacy continues to reverberate today. In this 'Very Short Introduction'
Includes Index and Illustrations.
Keywords: Epicureans (Greek philosophy)